Role of caffeic acid O-methyltransferase (COMT) in the interaction between oil palm and Ganoderma boninense - Tan, Wee Pheng (2016)
Caffeic acid O-methyltransferase (COMT) is a bifunctional enzyme that is responsible for methylation of a substrate at its 3-hydroxy and 5-hydroxy positions on the aromatic ring. This enzyme is involved in lignin biosynthesis pathway, with a particularly important role in supplying components for the synthesis of syringyl lignin units. Since lignin has been found to be highly associated with plant defence system, the aim of the present study is to investigate the relative expression levels of COMT in oil palm infected with Ganoderma boninense and to elucidate its involvement in oil palm defence response. The present study involves the design of primers for COMT gene in oil palm by using existing gene information from Genbank. The primer set was then used to examine and compare COMT expression levels between control, wounded and Ganoderma-infected oil palm seedlings via quantitative real-time PCR (qPCR). The effects of wounding and GBLS-inoculation that leads to pathogenesis on plant health (weight, height, stem diameter, root length and chlorophyll content) were also observed. Besides, a preliminary study which aimed to identify possible polymorphisms between COMT transcripts in oil palm seedlings subjected to normal, wounding and Ganoderma infection treatments were carried out. This was done by isolating, sequencing and comparing COMT transcripts from normal, wounded and GBLS-inoculated plants and subsequently aligned them using alignment software. Results from gene expression study showed that COMT transcripts in Ganoderma-infected plants were significantly increased (p < 0.05) to a level five-fold higher than the uninfected plants at 15 dpi. On the other hand, COMT in wounded plants was significantly up-regulated (p < 0.05) to 5.5-fold of that of the control at 12 dpi. Results from plant growth analyses showed that wounding and GBLS-infection had no significant effects on height, weight, stem diameter and chlorophyll content of the plant; while a slight but significant effect (p < 0.05) was detected on root length of the wounded plants. The preliminary polymorphism study also revealed that there was no putative polymorphism existed between COMT transcripts produced from control, wounded and infected seedlings. It is concluded that the significant up-regulation of COMT expression in response to wounding and G. boninense infection could enhance the defence system of oil palm via lignification.